2017
DOI: 10.1097/tp.0000000000001651
|View full text |Cite
|
Sign up to set email alerts
|

Practical Recommendations for Long-term Management of Modifiable Risks in Kidney and Liver Transplant Recipients

Abstract: Short-term patient and graft outcomes continue to improve after kidney and liver transplantation, with 1-year survival rates over 80%; however, improving longer-term outcomes remains a challenge. Improving the function of grafts and health of recipients would not only enhance quality and length of life, but would also reduce the need for retransplantation, and thus increase the number of organs available for transplant. The clinical transplant community needs to identify and manage those patient modifiable fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
97
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 243 publications
(116 citation statements)
references
References 398 publications
(606 reference statements)
0
97
0
7
Order By: Relevance
“…Rodrigo et al found that a higher intra-patient variability was independently related to development of donor-specific antibodies and graft-loss (Rodrigo et al, 2016). Identification of patients with a high intra-patient variability is therefore important as it is a modifiable risk factor, and interventions may improve longterm outcomes (Neuberger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rodrigo et al found that a higher intra-patient variability was independently related to development of donor-specific antibodies and graft-loss (Rodrigo et al, 2016). Identification of patients with a high intra-patient variability is therefore important as it is a modifiable risk factor, and interventions may improve longterm outcomes (Neuberger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce rejection episodes, graft loss and negative consequences of immunosuppressive medication renal transplant recipients are encouraged to acquire knowledge about medication regime, graft surveillance and the benefit of specific lifestyle behaviour (Firooz et al ; Kobus et al ; Neuberger et al ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Improvement of long-term outcomes after kidney transplantation remains a challenge ( 1 5 ). The most recent findings based on the United States registry data and Collaborative Transplant Study across 21 European countries, report only a slight improvement in renal allograft survival since the early 2000's ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%